ANALYSIS OF THE ANNUAL PLANNING PROCESS IN DINAS KESEHATAN PROVINSI DKI JAKARTA ON THE YEAR OF 2019 - Rahmalina, Septia; Basabih, Masyitoh (Journal of Indonesian Health Policy and Administration, 2021)
Planning is important in setting the basis for regulating and controlling the goals to be achieved from a system. The purpose of this research is to understand the annual planning process in Dinas Kesehatan Provinsi DKI Jakarta in the year 2019. The research is a descriptive study with qualitative methods. The data were collected through in-depth interviews and document review. This research found that the human resources (HR) of the existing planning staff were not in accordance with the needs. There was also no standard operational procedure (SOP) that regulates both in terms of planning HR needs and a more detailed planning process that could be used as a reference for planning staff in planning preparation. The researcher suggests that the planner's quality needs to be improved again, given adequate facilities and more detailed SOP development. Keywords: Planning is important in setting the basis for regulating and controlling the goals to be achieved from a system. The purpose of this research is to understand the annual planning process in Dinas Kesehatan Provinsi DKI Jakarta in the year 2019. The research is a descriptive study with qualitative methods. The data were collected through in-depth interviews and document review. This research found that the human resources (HR) of the existing planning staff were not in accordance with the needs. There was also no standard operational procedure (SOP) that regulates both in terms of planning HR needs and a more detailed planning process that could be used as a reference for planning staff in planning preparation. The researcher suggests that the planner's quality needs to be improved again, given adequate facilities and more detailed SOP development.